(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The clinical management of brain metastases arising from malignant tumors of internal organs has emerged as a significant topic in contemporary oncology. The diagnosis and therapy of metastatic lesions within the central nervous system have evolved over the last decades, leading to considerable improvements in patient care and outcomes. Brain metastases commonly complicate the natural history of cancers such as those of the lung, breast, kidney, gastrointestinal tract, and melanoma. The incidence of brain metastases continues to rise, largely due to improved systemic control of primary malignancies, enhanced survival rates, and advancements in neuroimaging methods that detect even small or asymptomatic lesions.